Prevalence and Determinants of Stunting Incidence in Toddlers - Tiorismasni Zai; Ermi Girsang; Sri Lestari Ramadhani Nasution; Chrismis Novalinda Ginting (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
The incidence of stunting in children under five is still the main cause of death in children under five in the world because the impact of stunting is not only on health problems but is closely related to the level of intelligence of children. This study aims to determine the prevalence and investigate the determinants of stunting in children under five. This study is quantitative research with a cross-sectional design. The population of this study was all mothers of children under five who visited the Mandrehe Barat Non-Inpatient Puskesmas in 2021, and the research sample was 200 mothers of children under five. Data was collected directly by distributing questionnaires to mothers of children under five. Then, continued with the process of data analysis with the chi-square test and binary logistic regression. The results showed that exclusive breastfeeding (p= less than 0.001; PR= 9.5; 95% CI 6.788-22.948), feeding patterns (p= less than 0.001; PR = 7.6; 95%CI 4.833-12.266), and consumption of vitamin A and zinc during pregnancy (p= less than 0.001; PR = 4.4; 95%CI 3.172-6.043) had a significant effect on the incidence of stunting, but a history of low birth weight (p= 0.785; PR= 1.08; 95% CI 0.372-3.306) and history of infectious disease (p=0.111; PR=1.5; 95%CI 0.978-2.441) were not significant for the incidence of stunting. Furthermore, the dominant factor in the incidence of stunting shows that toddlers who are stunted are 5.7 times more likely not to be given exclusive breastfeeding compared to toddlers who are not stunted. Thus, mothers of children under five are expected to take the time to visit health services by bringing their children under five to monitor their growth and development of children such as height and weight according to the child's age. Abstrak: Kejadian stunting pada anak balita hingga saat ini masih merupakan penyebab utama kematian pada anak balita di dunia, karena dampak stunting bukan hanya pada masalah kesehatan, namun, sangat erat kaitannya pada tingkat kecerdasan anak. Penelitian ini bertujuan untuk mengetahui prevalensi dan menyelidiki determinan kejadian stunting pada balita. Studi ini merupakan penelitian kuantitatif dengan desain crossectional. Populasi penelitian ini adalah seluruh ibu balita yang berkunjung di Wilayah Puskesmas Non Rawat Inap Mandrehe Barat Tahun 2021, dan sampel penelitian sebanyak 200 orang ibu balita. Pengumpulan data dilakukan secara langsung dengan menyebarkan kuesioner kepada ibu balita. Kemudian, dilanjutkan dengan proses analisis data dengan uji Chi Square dan regresi logistik biner. Hasil penelitian menunjukkan bahwa pemberian ASI Eksklusif (p=kurang dari 0,001;PR=9,5;95%CI 6,788-22,948), pola pemberian makan (p= kurang dari 0,001; PR=7,6; 95%CI 4,833-12,266), dan konsumsi vitamin A dan Zinc pada masa kehamilan (p= kurang dari 0,001;PR=4,4; 95%CI 3,172-6,043) berpengaruh signifikan terhadap kejadian stunting, namun riwayat BBLR (p=0,785; PR=1,08;95% CI 0,372-3,306) dan riwayat penyakit infeksi (p=0,111; PR=1,5; 95%CI 0,978-2,441) tidak signifikan terhadap kejadian stunting. Selanjutnya, faktor dominan terhadap kejadian stunting menunjukkan bahwa balita yang mengalami stunting 5,7 kali kecenderungannya tidak diberi ASI Eksklusif dibanding dengan balita yang tidak mengalami stunting. Dengan demikian, kepada ibu balita diharapkan agar melungkan waktu untuk berkunjung ke tempat pelayanan kesehatan dengan membawa anak balita untuk memantau tumbuh kembang anak seperti tinggi dan berat badan sesuai usia anak.